The New Orleans kitchen : classic recipes and modern techniques for an unrivaled cuisine - Devillier, Justin, 1981-; Feldmar, Jamie (Lorena Jones Books, an imprint of Ten Speed Press, 2019)
With its uniquely multicultural, multigenerational, and unapologetically obsessive food culture, New Orleans has always ranked among the world's favorite cities for people who love to eat and cook. But classic New Orleans cooking is neither easily learned nor mastered. More than thirty years ago, beloved Paul Prudhomme taught the ways of Crescent City cooking but, even in tradition-steeped New Orleans, classic recipes have evolved and fans of what is arguably the most popular regional cuisine in America are ready for an updated approach. With step-by-step photos and straightforward instructions, James Beard Award-winner Justin Devillier details the fundamentals of the New Orleans cooking canon--from proper roux-making to time-honored recipes, such as Duck and Andouille Gumbo and the more casual Abita Root Beer-Braised Short Ribs. Locals, Southerners, and food tourists alike will relish Devillier's modern-day approach to classic New Orleans cooking.